New Gynaecoserica Brenske, 1897 species and further new bicolored species of the Neoserica calva group (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk (Zootaxa, 2022)
In this paper, additional new species of Gynaecoserica Brenske, 1897 and the Neoserica calva group from continental Southeast Asia are described: Gynaecoserica krausi Ahrens, new species (Laos), G. obfuscata Ahrens, new species (Laos), Neoserica champassakensis Ahrens, new species (Laos), N. fairyqueen Ahrens, new species (Thailand), and N. samuelsoni Ahrens, new species (Laos). The habitus as well as the aedeagus of the new species are illustrated. New records of further species of the two genera are given.